Chromosome banding patterns in the unisexual microteiid gymnophthalmus underwoodi and in two related sibling species (gymnophthalmidae, Sauria) - Yonenaga-Yassuda, Yatiyo; Vanzolini, Paulo Emilio; Rodrigues, Miguel Trefaut; Carvalho, Celso Morato de (Cytogenetic and Genome Research, 1995)
Cytogenetic investigation of three species of the genus Gymnophthalmus (the unisexual G. underwoodi, G. leucomystax and Gymnophthalmus sp.n., a new, undescribed redtailed species) documented three different karyotypes, all with 2n = 44. Chromosomes from fibroblast cultures were studied after routine Giemsa staining, CBG-banding, RBG-banding, and Ag-NOR staining. The unisexual species showed a very distinctive karyotype from the one previously described that, paradoxically, corresponded to the predicted karyotype of one of its parental species. Our chromosome data unequivocally show that there are two parthenogenetic species with two different mechanisms of origin under the name underwoodi. © 1995 S. Karger AG, Basel.
Keywords: Animals Cell; Chromosome Banding Pattern; Chromosome Number; Female; Karyotype; Lizard; Male; Nonhuman; Priority Journal; Sex Determination; Sex Differentiation; Animals; Chromosome Banding; Female; Karyotyping; Lizards; Male; Nucleolus Organizer Region; Support, Non-u.S. Gov't